2003
DOI: 10.1046/j.1365-277x.2003.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting healthy diet and exercise patterns amongst primary school children: a qualitative investigation of parental perspectives

Abstract: Parents represent a potentially powerful intermediary in behaviour change strategies aimed at improving the lifestyle behaviours of young children. However, to fulfil this role, parents need to have the necessary knowledge and motivation to assimilate dietary guidelines. This study aimed to assess these psychosocial constructs, and subsequent parental receptiveness to nutrition education, through investigation of the barriers and benefits perceived by parents to the provision of a healthy diet and adequate exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
123
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(141 citation statements)
references
References 16 publications
16
123
0
2
Order By: Relevance
“…These findings suggest that intervention programmes may be enhanced by prioritising the 'how to prepare' messages and by including child behaviour management components over an emphasis on 'what to provide' information. These findings are consistent with findings with Australian parents of 2-5-year-olds (8) and 5-6-year-olds (16) , as well as UK parents of 7-12-year-olds (13) , that support the conclusion that while parents acknowledge their role or responsibilities around providing children with healthy food, support is needed to overcome barriers such as child/family resistance to a healthy diet, use of treats and lack of time/busy lifestyle.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings suggest that intervention programmes may be enhanced by prioritising the 'how to prepare' messages and by including child behaviour management components over an emphasis on 'what to provide' information. These findings are consistent with findings with Australian parents of 2-5-year-olds (8) and 5-6-year-olds (16) , as well as UK parents of 7-12-year-olds (13) , that support the conclusion that while parents acknowledge their role or responsibilities around providing children with healthy food, support is needed to overcome barriers such as child/family resistance to a healthy diet, use of treats and lack of time/busy lifestyle.…”
Section: Discussionsupporting
confidence: 93%
“…Canadian and British research also provides insights on parental attitudes and perceived barriers to physical activity in preschoolers (11) , attitudes to screenviewing behaviours in preschoolers (12) and attitudes to both eating and exercise in 7-12-year-olds (13) . Screen-viewing attitudes have also been investigated in American parents of 6-13-year-old children (14) .…”
mentioning
confidence: 99%
“…Studies have found parents not to be receptive to interventions aimed at specifically changing dietary behaviour, but are more motivated to engage in healthy behaviours and positive health beliefs within the family setting (11,12) . Hart et al suggest parent-targeted strategies should emphasize: (i) awareness-raising interventions such as promoting the acceptance of healthy foods and behaviours through repeated exposure techniques; (ii) encouraging family responsibility for diet and exercise rather than just providing parents with 'specific guidelines' to follow; and (iii) promoting dietary variety to tackle the myth of healthy eating as restrictive, expensive and unattainable (11) . Parents' knowledge of healthy foods and their child's food preferences related to healthy foods influenced food purchasing and preparation and parents balanced this with the barriers to healthy eating.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of belief in or understanding of the relationship between diet and disease may result in a lack of motivation to apply other aspects of nutrition knowledge; for example, knowledge of the nutrient content of foods or knowledge of dietary guidelines. Socio-economic groups are found to have different priorities and perspectives in relation to food choice decision making (49,50) . Concerns regarding health and nutrition are often reported to be more salient in the food choices of those of high SEP compared with those who are disadvantaged (50)(51)(52) .…”
Section: Nutrition Knowledge Componentmentioning
confidence: 99%